The Conceptual Foundation of Creation by Lombok Diaspora Artist in Contemporary Painting - Fitriani, Misva; Sucitra, I Gede Arya (Journal of Contemporary Indonesian Art, 2025)
The postmodern thought on pluralism influences contemporary art while providing opportunities for diaspora artists from Lombok to engage in it. This study aims to describe the foundational concepts and practices of diaspora artists from Lombok in the realm of contemporary art. The research method employed is qualitative, focusing on artists Saepul Bahri and Wisnu Aji Kumara, who have been active in the arts for over 14 years. The findings indicate that the artistic foundations of both artists are shaped by personal, social, and cultural experiences, as well as awareness of local values. Despite their differing approaches, both artists demonstrate a strong connection to Sasak traditions. Their concepts are enriched by aesthetic understandings gained from academic and non-academic environments, addressing contemporary issues within Sasak society while exploring cultural identity. Their works aim to apply Sasak aesthetic concepts of 'semaik' and 'pemolek'. This research documents the perspectives of diaspora artists from Lombok in understanding, adapting, or developing their creative concepts in a contemporary context, highlighting their contributions to expanding the narrative of contemporary art and maintaining the relevance of local culture in a global context.